Analisa Studi Literatur Manfaat Implementasi Komputasi Awan untuk Perusahaan - Heripracoyo, Sulistyo (Bina Nusantara University, 2014)
Cloud computing is a phenomenon that is currently a lot of attention from practitioners of information technology. Cloud computing can be composed of several types of services that are known to Saas, PaaS and IaaS, public and private cloud computing. Companies that do not invest themselves in the information technology infrastructure to use cloud computing services as a solution. By adopting and implementing a cloud computing services company can shift the cost of information technology infrastructure investments become operational costs by purchasing cloud computing services. Nevertheless, cloud computing, especially for the type of private cloud is still a bit of adopting it, whether it is caused by the absence of reference to the implementation or caused by something else. The purpose of this study was to analyze the adoption of cloud computing that suitable and beneficial for the company in its operational activities. The study was conducted by analysis of some of the literature related to cloud computing, benefits and barriers. According to the analysis of the literature can be explained some of the benefits associated with the adoption of cloud computing. Based on several studies that have been done, the benefits of implementing cloud computing is primarily financial savings and benefits of resource management that is the flexibility and scalability of the company's operations. However, some considerations still need to be done for a company that will implement cloud computing and those things are data security issues, legal issues and the implications for the company.